A new loach of the genus Physoschistura Bănărescu & Nalbant (Teleostei: Nemacheilidae) from Chindwin basin, Manipur, India - Lokeshwor, Y.; Vishwanath, W. (Zootaxa, 2012)
The paper describes Physoschistura tigrinum, a new nemacheilid from the Chindwin basin in Manipur, India. The newspecies is distinguished from congeners in having 9½ branched dorsal-fin rays; 12–14 irregularly arranged light reddishbrown bars on the side, some of which are broken into blotches and short bars; 5–6 dark brown saddles; forked caudal finwith 9+8 branched rays; axillary pelvic lobe well formed but not prominent; 10 pores in preoperculomandibular canal andsuborbital flap in the male. The status of Schistura prashadi is also discussed, and the species is validated to Physoschistura.